Stimulus-responsive light-harvesting complexes based on the pillararene-induced co-assembly of β-carotene and chlorophyll - Yan Sun (Nature Portfolio, 2016)
Carotenoids are photoactive organic pigments found in many plants. Here, the authors report the self-assembly of carotenoid suprastructures by forming a pillararene host-guest complex, and show that these structures display functionalities including stimuli responsiveness and photocatalytic activity.